Author Correction: Global land change from 1982 to 2016. (22nd November 2018) - Song, Xiao-Peng; Hansen, Matthew; Stehman, Stephen; Potapov, Peter; Tyukavina, Alexandra; Vermote, Eric; Townshend, John
In this Letter, errors in Supplementary Table 1 have been corrected.